Decolorization and detoxification of batik dye effluent containing Indigosol Blue-04B using fungi isolated from contaminated dye effluent - Ratna Stia Dewi; Rina Sri Kasiamdari; Erni Martani; Yekti Asih Purwestri (Universitas Gadjah Mada, 2018)
Fungi are capable of treating various synthetic dye effluents. Previously, we isolated seven strains of fungi from contaminated batik dye effluent at Banyumas, Central Java. The aims of this study were to screen the ability of these fungi to decolorize batik dye effluents containing Indigosol Blue-04B and to investigate the phytotoxicity effects of biodegraded effluent on the germination of corn seeds Zea mays L. and green bean seeds Vigna radiata (L.) Wilczek. In addition, the decolorized effluents were tested for toxic effect on the agriculturally important gram-positive and gram-negative soil bacteria Bacillus cereus and Azotobacter sp., Staphylococcus aureus and Escherichia coli, respectively. Study of decolorization showed that fungi were able to decolorize Indigosol Blue-04B batik dye effluents by 21.04% to 99.89% at room temperature after three days of incubation. The assay of phytotoxicity showed that both plumule and radicle length of Z. mays and V. radiata grown on the decolorized effluent was longer than on untreated effluent. The percentage of Z. mays and V. radiata seed germination in decolorized effluent was higher than in untreated effluent. There was no inhibition zone found around the decolorized effluent samples after incubating the bacteria for 48 hours. Aspergillus sp. 3 was the most effective for degradation and could be used for batik effluent mycoremediation processes.